Tall, Slim & Erect Portraits of the Presidents - Forman, Alex (punctum books, 2023)
After stumbling upon a wooden box containing a complete set of miniature wax mold figurines of US presidents at a flea market, artist Alex Forman began photographing each little man, minus their pedestals. Presented for the first time in book format, Forman's elegant black and white portraits are accompanied by brief biographies composed entirely of appropriated texts cleverly cut and reassembled by the author. What emerges in Tall, Slim & Erect: Portraits of the Presidents is not the tired tale of legendary men and their mythical quest for democracy, but rather, a gossip's dream: Jefferson could not ride a horse for months due to boils on his backside; Hayes felt a crazed and tender devotion to his sister Fanny; Wilson remained a virgin until twenty-eight. While playfully shedding light on these powerful men, their quirks, bodily functions, and stained sheets, Tall, Slim & Erect ultimately asks the reader to question how history is written and built on hearsay, conjecture, rumor, and repetition.